The Missing Part of Nuclear Power Plant Regulations in Turkey: Occupational Health and Safety - Limoncuoglu, S. Alp (Richtmann Publishing, 2012)
The researches made on X-rays and radioactive minerals prove that high level exposure to radiation results clinical harm onhuman tissues. Therefore, specific standards are needed to be implementing for the protection of workers who are exposed to radiationespecially in nuclear plants. Turkey is planning to activate its first nuclear power plant within couple of years. Accordingly, Turkey hassigned a contract for building its first nuclear power plant in Akkuyu, Mersin with Russian RosAtom. It will have an installed capacity of4.8 GW and expected to have a 5 per cent share in Turkey’s electricity generation. In addition, an intensive regulatory work has beendone by the Turkish Atomic Energy Authority. Most of them are in accordance with those of International Atomic Energy Agency. Theanalysis made in this study, however, shows that the occupational health and safety (OHS) of nuclear power plant workers is neglectedso far. Specific regulatory suggestions are made in order to raise the standards to international level.